2022
DOI: 10.3389/fnagi.2022.912691
|View full text |Cite
|
Sign up to set email alerts
|

Clinical determinants and neural correlates of presbyphagia in community-dwelling older adults

Abstract: Background“Presbyphagia” refers to characteristic age-related changes in the complex neuromuscular swallowing mechanism. It has been hypothesized that cumulative impairments in multiple domains affect functional reserve of swallowing with age, but the multifactorial etiology and postulated compensatory strategies of the brain are incompletely understood. This study investigates presbyphagia and its neural correlates, focusing on the clinical determinants associated with adaptive neuroplasticity.Materials and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…In terms of swallowing safety, a larger product could increase sensory perception, thus enhancing sensorimotor feedback as a compensatory mechanism. This is supported by previous clinical studies that have shown that intact pharyngeal sensation is important for a physiological swallowing process 28 , 29 . The findings on medication size contrast with a Food and Drug Administration (FDA) guidance document that considers the size of tablets or capsules to be a possible risk factor for dysphagia for medication and therefore recommends the production of small products.…”
Section: Discussionsupporting
confidence: 85%
“…In terms of swallowing safety, a larger product could increase sensory perception, thus enhancing sensorimotor feedback as a compensatory mechanism. This is supported by previous clinical studies that have shown that intact pharyngeal sensation is important for a physiological swallowing process 28 , 29 . The findings on medication size contrast with a Food and Drug Administration (FDA) guidance document that considers the size of tablets or capsules to be a possible risk factor for dysphagia for medication and therefore recommends the production of small products.…”
Section: Discussionsupporting
confidence: 85%
“…Swallowing impairment is common in most neurological disorders such as stroke, Parkinson's disease, dementia, neuroinflammatory diseases, and neuromuscular disorders, but can also occur in healthy older people. [1][2][3][4][5][6][7][8][9][10] Often, the oral and pharyngeal phases of swallowing are affected simultaneously, which is characterized as oropharyngeal dysphagia.…”
Section: Introductionmentioning
confidence: 99%
“…With aging, many changes are involved, such as reduced muscle mass, lower saliva production, reduced sense of taste and smell [ 1 3 ], and less coordination between swallowing and respiratory functions [ 4 ]. These age-related physiological changes in the swallowing mechanism correspond to presbyphagia and are not considered pathological [ 5 ]. Presbyphagia can be responsible for changes in eating habits, with the implementation of compensatory strategies by the elderly, such as reducing the quantities ingested [ 6 ].…”
Section: Introductionmentioning
confidence: 99%